The Effectiveness of Cognitive Behavior Therapy (CBT) in Overcoming Various Anxieties - Putra Suharnadi; Netrawati; Zadrian Ardi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Anxiety is a form of affective disorder characterized by deep and persistent feelings of fear or worry, no disturbance in assessing reality, behavior can be disturbed but still within normal limits. Academic anxiety is a problem that stems from negative thoughts that will affect students' academic achievement. In the treatment of anxiety disorders, cognitive-behavioral therapy can help to identify and challenge an individual's negative thought patterns. Cognitive Behavioral Therapy (CBT) is the first therapeutic approach that focuses on the process of thinking and is related to emotional, behavioral, and psychological states. , CBT techniques help someone identify cognitive patterns or thoughts and emotions related to their behavior Based on cognitive theory, the way of thinking determines how a person feels and acts. CBT is centered on the idea that certain people are able to change their understanding, and therefore change the impact of thinking on their emotional well-being. The CBT approach is effective in reducing an individual's anxiety levels. Cognitive-Behavioral Therapy is based on the formulation of cognitive, beliefs and behavioral strategies that characterize certain disorders. In several studies, CBT has been found to be effective in reducing anxiety in various groups, such as: Adolescents, Elderly, Students and students.